Genetic Variability and Correlation Studies in Selected Maize (zea mays l.) Genotypes during the Seedling Stage in Jos, Nigeria. (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
The study aimed to determine the extent of genetic variability and diversity for drought tolerance traits present in 24 maize genotypes in order to aid parents in selecting superior recombinant F1 genotypes. Six seeds of each maize genotype were sown in 45cm x 10cm polyvinyl chloride (PVC) pipes filled with a loamy soil potting mixture. Before seeding, moisture was kept at field capacity. Seedlings were thinned to four per pot after emergence and arranged in a Complete Randomized Design that was replicated three times. The experiment was adequately watered daily for the first 15 days, after which watering was discontinued. Morphophysiological data on seedling water use efficiency was collected and analyzed. Before conducting ANOVA, data normality and variance homogeneity were assessed using the Shapiro-Wilk and Levene’s tests, respectively. For all traits studied, there were significant differences between genotypes. Cluster analysis using Morphophysiological traits separated genotypes into three distinct groups while Pearson correlation method was used for the correlation analysis. The genotypic and phenotypic coefficients of variation revealed a high degree of variability. Very high genetic advance and heritability values were observed. The results indicate sufficient genetic variability and diversity among the genotypes. Integrated analysis of genetic parameters and trait performance identified several promising parental lines for drought tolerance improvement, including KIERKIER, TZM-DAFFO–L, KAF16, MARA AURE–W, SAMMAZ-52, OBA SUPER II, and PVA–SYN lines. These genotypes hold potential for use in future drought-tolerant crop improvement programs.